STUDENTS' PERCEPTIONS OF WHAT INSTRUCTORS DO TO HELP STUDENTS LEARN IN THE CLASSROOM - Parrish, Denise (My University, 2009)
Currently, there are few available research studies examining students' perceptions of what instructors do to help students learn in the classroom. The purpose of this study was to explore and describe how students in a baccalaureate nursing degree program perceive how instructors help them learn in the classroom. The goal was to provide nursing instructors and nursing education administrative teams with positive educational strategies, based on student perceptions, for teaching in the classroom. Dunkin and Biddle's (1974) Model of the Study of Classroom Teaching was used as the conceptual framework to guide this study. The model describes the many variables that contribute to the instructor and learner experience and also explains how these variables can affect the perceptions and outcomes for the learner and the instructor. A descriptive qualitative design was used. A convenience sample of 21 senior level nursing students from a college of nursing in the Midwestern United States comprised the sample. Informed consent was obtained from the volunteer sample. A demographic questionnaire was completed along with an unstructured interview. Interviews were tape recorded and transcribed verbatim. Data were analyzed using Colaizzi's method. Results indicated that the sample was comprised of participants ranging in age from 21 to 46 years, with a mean age of 25 years and a mode of 22 years. Three of the participants were male and 18 were female. Twelve of the participants (57%) were in the first semester of their senior year, and the remaining 9 participants (43%) were in the second semester of their senior year. Data analysis revealed that perceptions of what instructors do to help students learn were diverse. The four major themes identified coincide with the presage variables, teacher properties, of Dunkin and Biddle's Model for the Study of Classroom Teaching (Figure 1): (a) teaching skills, (b) intelligence, (c) motivations, and (d) instructor personality traits. By understanding the perceptions of senior level nursing students, nursing instructors and nursing education administrative teams can provide students with positive education strategies for teaching in the classroom. Findings may also have implications for future nursing students and curricula in nursing education master degree programs.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science in Nursing Nurse Educator
Keywords: Communication in education; Feedback (Psychology); Teacher-student relationships